Pengaruh Kepuasan Kerja Terhadap Kinerja Individual dengan Self Efficacy sebagai Variabel Intervening - Choirunissa, Alfania; Prayekti, Prayekti; Septyarini, Epsilandri (Jurnal Ilmiah Manajemen Kesatuan, 2020)
This study aims to determine the effect of job satisfaction on individual performance with self-efficacy as an intervening variable for employees of PT Nusantara Surya Sakti Yogyakarta. This type of research used in this research is descriptive quantitative. The population used is all employees of PT Nusantara Surya Sakti Yogyakarta as many as 55 employees. The sample in this study were all employees of PT Nusantara Surya Sakti Yogyakarta, as many as 55 employees. The sampling technique used was total sampling with data collection methods using a questionnaire. The data analysis technique in this study used simple linear regression. Based on the results of this study, job satisfaction has no significant positive effect on individual performance. Job satisfaction has significant positive effect on self efficacy and self efficacy has significant positive on individual performance. In this study, self efficacy as an intervening variable has a significant positive effect on job satisfaction on individual performance. Keywords : Job Satisfaction, Individual Performance, and Self Efficacy